Analysis of Farmers’ Awareness Level Toward the Use of Personal Protective Equipment (PPE) - Enggal Hadi Kurniyawan; Imel Ajeng Lestari; Elysa Apriliani; Julian Ferdinanda Prasetya Eryata; Alfid Tri Afandi; Dicky Endrian Kurniawan; Kholid Rosyidi Muhammad Nur; Ikha Nurjihan; Yopi Darmawan; Elok Faradisa (Health and Technology Journal (HTechJ), 2025)
The use of pesticides in agriculture increases crop yields, but poses health risks to farmers, especially without PPE. Global data shows a high rate of pesticide poisoning, especially in developing countries. In Indonesia, farmers' awareness and compliance with the use of PPE are still low due to factors related to education, training, and risk perception. This study aims to analyze the level of awareness among farmers regarding the use of PPE and the factors that influence their occupational safety practices when using pesticides. This study employed a literature review method, searching articles from three electronic databases: PubMed, ScienceDirect, and SpringerLink. The selection of articles was carried out in stages based on the keywords used "farmers" OR "agricultural workers" AND "awareness" OR "knowledge" OR "perception" AND "personal protective equipment" OR "PPE" AND "use" OR "utilization" OR "practice" AND "analysis" OR "study" OR "assessment", until 12 primary articles were analyzed in depth. The results show that the use of personal protective equipment (PPE) remains relatively low and inconsistent, despite most individuals having received training and sufficient knowledge. There is a gap between knowledge and practice of PPE use among tobacco farmers, which is influenced by various social and structural factors. Educational interventions based on behavioral models, cross-sectoral involvement, and the provision of adequate PPE are essential to improve farmers' work safety sustainably.